2023
DOI: 10.3390/ijms24043747
|View full text |Cite
|
Sign up to set email alerts
|

ERβ1 Sensitizes and ERβ2 Desensitizes ERα-Positive Breast Cancer Cells to the Inhibitory Effects of Tamoxifen, Fulvestrant and Their Combination with All-Trans Retinoic Acid

Abstract: Adjuvant endocrine therapy (AET) is the treatment of choice for early-stage estrogen receptor alpha (ERα)-positive breast cancer (BC). However, almost 40% of tamoxifen-treated cases display no response or a partial response to AET, thus increasing the need for new treatment options and strong predictors of the therapeutic response of patients at high risk of relapse. In addition to ERα, BC research has focused on ERβ1 and ERβ2 (isoforms of ERβ), the second ER isotype. At present, the impact of ERβ isoforms on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
0
0
0
Order By: Relevance
“…Moreover, this SI covers several in vitro studies that investigated different human cell types [13][14][15][16][17][18][19]. Two such publications used data sourced from animal experiments [15,19].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this SI covers several in vitro studies that investigated different human cell types [13][14][15][16][17][18][19]. Two such publications used data sourced from animal experiments [15,19].…”
mentioning
confidence: 99%
“…Meligova et al [16] conducted a pharmacological study that investigated MCF-7 BC cells and their responses to antiestrogens and retinoids [16]. The authors showed that ERβ1 is a marker of responsiveness; in contrast, ERβ2 was shown to be an indicator of MCF7 cells' resistance to antiestrogens alone and in combination with all-trans retinoic acid (ATRA) [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation